2002
DOI: 10.1055/s-2002-20174
|View full text |Cite
|
Sign up to set email alerts
|

Air Emboli in the Intracranial Venous Sinuses of Neonates

Abstract: Air bubbles in the intracranial venous sinuses are known as a consequence to different causes including trauma, infection, and administration of intravenous contrast. Most of the previous reports demonstrated such cases in adults, with subsequent complications. We are presenting two premature babies who developed asymptomatic air bubbles in the right cavernous and left transverse sinuses, introduced accidentally upon cannulation of scalp veins. In both babies the air embolism disappeared in a few days without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The air encountered in the right heart may well have entered via these two peripheral catheters as demonstrated in our experimental setup. Accidental air entrance via peripheral veins has also been reported in the literature [8,9].…”
Section: Discussionmentioning
confidence: 80%
“…The air encountered in the right heart may well have entered via these two peripheral catheters as demonstrated in our experimental setup. Accidental air entrance via peripheral veins has also been reported in the literature [8,9].…”
Section: Discussionmentioning
confidence: 80%
“…CT has been used to detect retrograde cerebral venous air emboli in both the pediatric and adult populations. Additional reports have described antegrade cerebral venous air emboli in neonates after scalp vein cannulation in which air was introduced into the intracranial venous sinuses via the epicranial emissary veins [4] , [5] . Two cases were detected with CT at 4 and 12 weeks of age [4] , and one was detected with ultrasonography at day 5 [5] .…”
Section: Discussionmentioning
confidence: 99%
“…6 Air has been reported within cerebral vessels 13,18,24 and in two instances within the intracranial venous sinuses with survival of the infants. 25 Rupture of alveoli into pulmonary capillaries due to barotrauma through alveolar-capillary or bronchovenous fistulae is thought to be the main cause of massive air embolism in infants with an air leak. 2,4,5,7,10,26 Systemic venous air was found always to be predominant over systemic arterial air in the study of Booth et al, 27 in which it was shown that PIE was statistically more prevalent than pneumomediastinum and/or pneumopericardium and was similar in prevalence to pneumothorax.…”
Section: Discussionmentioning
confidence: 99%